Shipboard Guardian: Sistem IoT untuk Pemantauan Suhu dan Kelembaban Ruangan Kelistrikan Kapal - Jumrianto, Jumrianto; Hariningrum, Rita; Purnamasari, Dewi; Rosyihin, Ashof (Politeknik Bumi Akpelni Semarang, 2026)
The electrical system on a ship is a critical area vulnerable to system failure and fire risks due to excessive temperature or humidity. This research aims to design and implement a remote temperature and humidity monitoring system called